(untitled) (Journal of Informatics Education and Research, 2024)
The present paper aims at examining the implication of a blockchain system in the financial markets and its function in enhancing security measures and economic transactions. An intricate analysis was conducted on four algorithms: Cryptographic Hash Function for secure transaction, Consensus Mechanism for achieving consensus in the blockchain, how smart Contracts work for the Blockchain, and Distributed Ledger Technology which is the basis for the blockchain transactions. The efficiency of these algorithms was tested and evaluated on an experimentally simulated dataset of 1000 financial transactions. The findings suggest a 30% total reduction of the number of times patients engage in a transaction with the system. It also has a 25% recoil rate in fraud than the conventional systems in its place. The integration of blockchain in the system is also seen to increase operational efficiency by 40% and stakeholder trust by 50%. These are all the evidences showing the potentials that exist in blockchain, transforming the way financial institutions practice for economic sustainability. Therefore, the conclusion of this research is that, even though great benefits accrue from the usage of blockchain, there exist numerous challenges based on regulation and ethics in terms of addressing the practicalities of its spread.